2020
DOI: 10.1093/cid/ciaa351
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Prolonged Viral RNA Shedding in Patients with Coronavirus Disease 2019 (COVID-19)

Abstract: Background. An outbreak of coronavirus disease 2019 is becoming a public health emergency. Data are limited on the duration and host factors related to viral shedding.Methods. In this retrospective study, risk factors associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA shedding were evaluated in a cohort of 113 symptomatic patients from 2 hospitals outside Wuhan.Results. The median (interquartile range) duration of SARS-CoV-2 RNA detection was 17 (13-22) days as measured from illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

65
533
22
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(629 citation statements)
references
References 26 publications
65
533
22
9
Order By: Relevance
“…Our search for COVID-19, SARS and MERS identified 5120 citations. After removing duplicates, screening titles and abstracts, and reviewing full texts, we ultimately included 1 cohort study 8 including 84 patients with COVID-19 and ARDS, 5 cohort studies [19][20][21][22][23] including 679 patients with COVID-19 but without ARDS, 3 studies (2 cohort studies 24,25 and 1 RCT 26 ) including 7087 patients with SARS, and 2 cohort studies 27,28 including 623 patients with MERS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search for COVID-19, SARS and MERS identified 5120 citations. After removing duplicates, screening titles and abstracts, and reviewing full texts, we ultimately included 1 cohort study 8 including 84 patients with COVID-19 and ARDS, 5 cohort studies [19][20][21][22][23] including 679 patients with COVID-19 but without ARDS, 3 studies (2 cohort studies 24,25 and 1 RCT 26 ) including 7087 patients with SARS, and 2 cohort studies 27,28 including 623 patients with MERS.…”
Section: Resultsmentioning
confidence: 99%
“…One cohort study 20 reported an increase in the composite outcome of mortality or ICU admission with steroid use. Two cohort studies 21,22 suggested that corticosteroids use was associated with prolonged viral shedding (very low-quality evidence).…”
Section: Severe Covid-19: Direct Evidence From Observational Studiesmentioning
confidence: 99%
“…1 Novel coronavirus disease (COVID-19) has spread to more than 200 countries, and the death toll remains very high. 2 According to some retrospective analyses, the median duration of viral shedding was 12-20 days from illness onset, [3][4][5] whereas the longest duration recorded has been 49 days. 6 We present a case of COVID-19 with viral shedding for 60 days from the onset of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Methylprednisolone was the most frequently used corticosteroid (13/22 studies). [33,[37][38][39][40][42][43][44]46,[48][49][50][51] In two studies methylprednisolone, hydrocortisone, or dexamethasone was used. [36,41] Ling et al used prednisolone or dexamethasone, [52] and Horby et al reported on dexamethasone use.…”
Section: Resultsmentioning
confidence: 99%
“…In four of these, mortality was only described in the overall study population and not speci ed for steroid or non-steroid study groups. [41,51,54,55] Two studies reported that corticosteroid treatment did not signi cantly affect mortality, without the possibility to quantify the effect. [42,43] In the remaining eight studies, the risk of corticosteroid use was quanti ed, and these were included to calculate the pooled estimate.…”
Section: Resultsmentioning
confidence: 99%